Strategi Mahasiswa Tentang Dampak Toxic Parents Bagi Kesehatan Mental Anak di Usia Dini - Br Sembiring, Andini; Ramadhani Sitorus, Laila Atiyyah; Fadhillah, Zaki (PT. Alahyan Publisher Sukabumi, 2025)
In toxic parenting, parents treat their children in ways that are inappropriate for them as individuals, such as not supporting their work or pointing out things that the child has done in daily life. A person who likes to compare the child with other children or with their own siblings to illustrate the child's lack of self-confidence. A person who likes to compare the child to other children or to their own siblings respectively illustrates the child's lack of self-confidence. The toxic parent of the person or other parent who performs the behavior has bad behavior, such as physical and verbal abuse, so that in the end the person becomes toxic in the child's personal life and it is something that is consciously noticed by the parent. Children with toxic parents suffer severe negative effects. Children are capable of mental memorization. The submissive type will be able to work quickly to help others by fulfilling all can work quickly to help others by fulfilling all their wishes. their wishes. On the other hand, the rebellious type of child will be a boon to the individual.On the other hand, the rebellious type of child will be a boon to the individual. If toxic parents negatively impact the lives of their children over a long period of time, their mental health will be compromised negatively impact the lives of their children over a long period of time, their mental health will be compromised. If a child's mental health is compromised, it will affect their behavior in daily life. If it is compromised, it will affect the way they behave in their daily lives.